Performance improvement of the shredder machines using IoT-based overheating controller feature - Emy Setyaningsih; Satriawan Dini Hariyanto; Dewi Wahyuningtyas; Samuel Kristiana (JURNAL INFOTEL, 2022)
Plastic shredding plays an essential role in the plastic waste recycling process. Plastic waste can be enumerated manually using a knife and scissors or a crushing machine. The use of a shredder machine to chop plastic waste, especially those whose primary drive is an electric motor, often experience problems. The main obstacle is the need for high power consumption (more than 1 HP) and the reliability of the drive elements against overheating. Overheating can damage the electrical circuit components that connect the power supply to electric motors, especially AC electric motors, causing a lot of loss in terms of performance and user safety. Internet of Things (IoT) technology is widely used to minimize energy resources by automating various systems. This study proposed the design of a shredder machine with a control system using IoT technology integrated with a shredder and conveyor machine designed using the Quantity Functional Diagram (QFD) method. The advantages of the shredder machine presented in this study are that it can operate at home using electric power, is more flexible, and minimizes overheating with an IoT-based overheating controller. This research succeeded in keeping the temperature of the electric motor of the shredder machine stable at a temperature of 40℃-55℃. The average delay of the IoT module to control on and off the shredder machine design system in this study is 219 ms and 200 ms, which are in the good category according to the Telecommunications and Internet Protocol Harmonization Over Network (TIPHON) standard.